2016
DOI: 10.1142/s0218495816500023
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Market and Entrepreneurial Orientation and Organizational Performance: Empirical Evidence from Small and Medium Scale Garment Manufacturers in Sri Lanka

Abstract: The literature indicates that small and medium scale firms are quite different with respect to their utilization of business practices. Thus, the study endeavours to address the relationships between the market and entrepreneurial orientation, and organizational performance. The study derived two hypotheses in relation to the relationship between market orientation and entrepreneurial orientation, and organisational performance in the attempt to examine how both the orientations contribute to the organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
1
12
0
2
Order By: Relevance
“…Hult et al (2004) and Lumpkin and Dess (1996) in Wijesekara et al (2014) states that entrepreneurial orientation is a process, practice and decision making activity that leads to entrepreneurship. Drucker (1994) defines an entrepreneurial orientation as a character or trait attached to the real business world and can develop them with resilience.…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hult et al (2004) and Lumpkin and Dess (1996) in Wijesekara et al (2014) states that entrepreneurial orientation is a process, practice and decision making activity that leads to entrepreneurship. Drucker (1994) defines an entrepreneurial orientation as a character or trait attached to the real business world and can develop them with resilience.…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
“…In the organizational performance literature model, several aspects are used as indicators to measure organizational performance. According to Brett (2000) in Wijesekara et al (2014), company performance covers three main aspects, namely output or performance operating (for example finance, productivity, and efficiency), outcome or delivery performance (eg effectiveness, strategy, and quality) and process performance (involving both operating performance and delivery performance). Venkatraman and Ramamujam (1986) state that company performance using perspective is operational performance measured through market share, new product introductions, marketing effectiveness, and various measures of technological efficiency related to business performance.…”
Section: Companymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Reference [25] stated that market orientation has a positive and significant impact on the performance of SMEs in Malaysia. The same thing is also refrence [6] stated that market orientation has a positive and significant role on marketing performance as shown in Figure 1. Based on previous research, the link between market orientation and marketing performance.…”
Section: Framework Thinking and Hypothesismentioning
confidence: 94%
“…al., 2009). A number of studies have shown that entrepreneurial orientation either directly or indirectly has a positive relationship with company performance (Wijesejara, et. al., 2014;Meutia, 2013;Pratono, et.…”
Section: Relationship Of Entrepreneurial Orientation With Company Permentioning
confidence: 99%